Analysis of the Influence of Change Oriented Leadership and Perceptions of Organizational Support on Employee Loyalty at Mahkota Group - Rianto Manurung (SEAN Institute, 2022)
This study is to determine the influence between leadership orientation change and the perception of organizational support with customer loyalty of the Mahkota Group. This study is a descriptive quantitative questionnaire instrument. The study population is all customers who repeatedly visit The Crown Group with a saturated sample technique then a sample of 40 people. Data analysis techniques in the form of instrument quality tests, classical assumptions, multiple linear regression, self and simultaneous tests and determinant coefficients. The results of the study are, leadership orientation change 3.675, table value 2.022; ttable value > ttable and sigcount < sigtable (3.675 > 2.022) and (0.000 < 0.05). The value of the perception of organizational support is 5.037, the value of table is 2.022. Rsquare value is 0.724 or R2 x 100% which is 72.